Do negative interest rates make banks less safe? - Federico Nucera; Andre Lucas; Julia Schaumburg; Bernd Schwaab (European Central Bank (ECB), 2017)
We study the impact of increasingly negative central bank policy rates on banks' propensity to become undercapitalized in a financial crisis ('SRisk'). We find that the risk impact of negative rates is moderate, and depends on banks' business models: Banks with diversified income streams are perceived by the market as less risky, while banks that rely predominantly on deposit funding are perceived as more risky. Policy rate cuts below zero trigger different SRisk responses than an earlier cut to zero.
Keywords: G20; G21; 330; negative interest rates; bank business model; systemic risk; unconventional monetary policy measures